DNA Methylation in Prostate Cancer: Clinical Implications and Potential Applications - Romane Muletier; Céline Bourgne; Laurent Guy; Aurore Dougé (Cancer Medicine)
ABSTRACT Background Prostate cancer is a common cancer with a variable prognosis. Its management is currently guided by histological and biological markers such as the Gleason score and PSA. Developments in molecular biology are now making it possible to identify new targets for better classification of prostate cancer. Among emerging biomarker, DNA methylation, an epigenetic process, is increasingly being studied in carcinogenesis. Techniques for analyzing DNA methylation are constantly improving, and digital PCR now allows absolute methylation quantification with high sensitivity. These techniques can be performed on circulating tumor DNA. Materials & Methods We conducted a literature review of scientific articles addressing the topic of DNA methylation in prostate cancer. Results & discussion This review summarizes the different genes whose methylation is involved in carcinogenesis and their clinical implications, both diagnostic and prognostic. Methylation monitoring could also be useful for the prediction of treatment response. However, most studies are retrospective, and prospective studies are needed to validate these data.